2017
DOI: 10.1371/journal.pone.0167412
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Antioxidant System in a Long-Lived Termite Queen

Abstract: The trade-off between reproduction and longevity is known in wide variety of animals. Social insect queens are rare organisms that can achieve a long lifespan without sacrificing fecundity. The extended longevity of social insect queens, which contradicts the trade-off, has attracted much attention because it implies the existence of an extraordinary anti-aging mechanism. Here, we show that queens of the termite Reticulitermes speratus incur significantly lower oxidative damage to DNA, protein and lipid and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 47 publications
8
55
2
Order By: Relevance
“…In addition, vitellogenin is known to act as an antioxidant that promotes survival in honeybee queens (Seehuus et al ., ; Corona et al ., ). Antioxidant systems are thought to be associated with termite survival and also fecundity (Tasaki, Kobayashi et al ., ; Tasaki, Sakurai et al ., ). We found that, under hypoxic conditions, queens exhibited more than five times higher expression levels of RsCAT1 at 2 weeks than at 1 day (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, vitellogenin is known to act as an antioxidant that promotes survival in honeybee queens (Seehuus et al ., ; Corona et al ., ). Antioxidant systems are thought to be associated with termite survival and also fecundity (Tasaki, Kobayashi et al ., ; Tasaki, Sakurai et al ., ). We found that, under hypoxic conditions, queens exhibited more than five times higher expression levels of RsCAT1 at 2 weeks than at 1 day (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A). As demonstrated in a previous study, a high level of RsCAT1 expression is a major characteristic of mature queens and may play an important role in the antioxidant system (Tasaki, Kobayashi et al ., ). On the other hand, kings exhibited more than twice the expression levels of RsPHGPX at 2 weeks than at 1 day under hypoxic conditions (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The queens live 10–100 times longer than the workers (Tasaki et al . ,b). A termite queen can live up to 20 years (Makrushin ) and even 30 years (Keller ).…”
Section: Use Of Termites In Scientific Studiesmentioning
confidence: 99%